2019
DOI: 10.1111/bld.12265
|View full text |Cite
|
Sign up to set email alerts
|

Adults with intellectual disability and Attention Deficit Hyperactivity Disorder: Clinical characteristics and medication profiles

Abstract: Accessible summary• Attention deficit hyperactivity disorder (ADHD) is often missed/underdiagnosed in people with intellectual disability compared to people without intellectual disability.How to cite this article: Al-Khudairi R, Perera B, Solomou S, Courtenay K. Adults with intellectual disability and ADHD:Clinical characteristics and medication profiles. Br J Learn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…Similar to other published studies, we also found that ADD was more common among autistic adults without ID (Bishop-Fitzpatrick & Rubenstein, 2019). One possible explanation for this finding may be that, among those with ID, ADDs may be more difficult to diagnose due to diagnostic overshadowing (Al-Khudairi et al, 2019). The higher prevalence of ADDs among autistic older adults without ID may also explain the increased risk of substance use disorders among this group, as prior studies have shown that substance use disorders are most common among autistic adults who have a co-occurring ADD diagnosis (Butwicka et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to other published studies, we also found that ADD was more common among autistic adults without ID (Bishop-Fitzpatrick & Rubenstein, 2019). One possible explanation for this finding may be that, among those with ID, ADDs may be more difficult to diagnose due to diagnostic overshadowing (Al-Khudairi et al, 2019). The higher prevalence of ADDs among autistic older adults without ID may also explain the increased risk of substance use disorders among this group, as prior studies have shown that substance use disorders are most common among autistic adults who have a co-occurring ADD diagnosis (Butwicka et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, it was already suggested that the diagnosis of ADHD is often missed or misdiagnosed in people with ID as ADHD can be missed and the behaviours attributed to the ID or autism (Perera 2018; Al‐Khudairi et al . 2019). Another reason is that scientific evidence available on the pharmacological treatment of ADHD in DS is limited to case reports and an open‐label trial of guanfacine (Capone et al .…”
Section: Discussionmentioning
confidence: 99%
“…This also might help to reduce the use of psychotropic medications such as antipsychotics (Al‐Khudairi et al . 2019). Moreover, the association of ADHD with ODD is frequent and complicates the life of these children and their families and contributes to learning difficulties and lack of social inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…This view could, in turn, contribute to the debate as to why some (but not all) individuals with impaired selective attention, such as ADHD (Brodeur & Pond, 2001;Mueller, Hong, Shepard, & Moore, 2017), perform poorly on the achievement and IQ tests (Frazier, Demaree, & Youngstrom, 2004). Validation of this hypothesis deserves further investigation, particularly given that learning difficulties with reading/arithmetic and attention deficits are often understudied or underestimated in people with borderline intellectual functioning (Al-Khudairi, Perera, Solomou, & Courtenay, 2019;Baglio et al, 2014;Di Blasi, Buono, Cantagallo, Di Filippo, & Zoccolotti, 2019;Jansen, De Lange, & Van der Molen, 2013;E. Rose, Bramham, Young, Paliokostas, & Xenitidis, 2009); such individuals are not often granted eligibility to access specialized healthcare or social/educational services they might need (Martinez & Quirk, 2009).…”
Section: Reho In Thalamus/pulvinarmentioning
confidence: 98%